Implementation Of Productive Zakat In The Digitalization Era In Indonesia - Hanik, Umi; Hendry Hermawan Adinugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
In this modern era, technology has developed rapidly. Technological developments are used in various fields of life. In Indonesia itself, one of the fields that takes advantage of technological developments is zakat. Digital Zakat is an innovation carried out by the Amil Zakat Institution to maximize the potential of existing zakat. This research is research with qualitative methods. This research method uses a library approach that originates from books and journals that are appropriate to the topic and research focus. The results of this study state that digital zakat innovations can help Amil Zakat Institutions to collect zakat from Muzakki. Digital zakat will also make it easier for Muzakki to see how the Amil Zakat Institution manages the assets it issues.